Evaluation of optimum adsorption conditions for Ni (II) and Cd (II) removal from aqueous solution by modified plantain peels (MPP) - N. Garba, Zaharaddeen; I. Ugbaga, Nkole; K. Abdullahi, Amina (Elsevier, 2016)
The most ideal conditions for the adsorption of Ni (II) and Cd (II) ions onto modified plantain peel (MPP) from aqueous solution were investigated. The effects of three adsorption variables (pH, MPP dose and initial adsorbate concentration) were studied using central composite design (CCD), a subset of response surface methodology (RSM). Quadratic models were developed for both Ni (II) and Cd (II) percentage removals. The prime adsorption conditions obtained were pH of 4.36, MPP dose of 0.82 g and initial concentration of 120 mg/L with desirability of 1.00 which gave good monolayer adsorption capacities of 77.52 and 70.92 mg/g for Ni (II) and Cd (II) respectively. The adsorption data were modelled using Langmuir and Freundlich adsorption isotherms; the equilibrium adsorption of both Ni (II) and Cd (II) on MPP obeyed Langmuir model, and pseudo-second-order kinetics was the order that best described the two adsorption processes.